Peningkatan Prestasi Belajar Mata Pelajaran Bahasa Inggris melalui Penerapan Card Sort Learning - Nurul Hidayati (Medan Resource Center, 2022)
In the right learning method must be applied to maximize students' abilities during learning activities. This study aims to determine the improvement of learning achievement in English through the application of the card sort method. An action study (action research) was carried out on learning English material on Verb for 7th grade students of SMPN 2 Gempol, Gempol District, Pasuruan Regency, for the 2021/2022 Academic Year. Indicators The results showed that the percentage of mastery learning at the pre-cycle stage was 10.7%, in the first cycle it was 67.9%, and in the second cycle it reached 92.9%. The average score of student test results also experienced a significant increase, namely the pre-cycle stage was 58.8, the first cycle was 72.4, and in the second cycle it rose to 78.9. This means, through the application of card sort learning can improve student achievement in learning English Verb material.